Manufacturing Flexibility through Industry 4.0 Technological Concepts—Impact and Assessment - Kristina Höse; Afonso Amaral; Uwe Götze; Paulo Peças (Global Journal of Flexible Systems Management, 2023)
There is an ever-growing need for companies and manufacturing systems to be flexible in order for them to adapt to the rapid changes and increasing uncertainty in society, markets, and supply chains. Several studies suggest that Industry 4.0 solutions foster shorter innovation/development cycles, resource efficiency, individualization on demand, faster decision making, and, finally, higher flexibility in production. However, little is still known about the relationship between Industry 4.0 and manufacturing flexibility. One of the existing gaps in the literature is the lack of a methodology to assess the potential impact of Industry 4.0 solutions on manufacturing flexibility and companies' profitability. This paper contributes to closing such a gap from a theoretical perspective. First, it conceptualized the role of flexibility in manufacturing systems. Then, the relationship between Industry 4.0 solutions and manufacturing flexibility was analyzed on a conceptual level, in which the I–T–O model was used to distinguish between the needed and available flexibility. Lastly, based on a decision-theory-based procedure model, a methodological approach for evaluating Industry 4.0 solutions is suggested. This methodological approach is intended to support transparent assessments tailored to different technological concepts as well as the affected types of flexibility (available and needed). It is able to integrate existing methods from decision and investment appraisal theory as well as specific flexibility-related approaches. The results of the paper will be useful for both academicians and practitioners. Besides enabling quantitative evaluations, the methodological approach can be used by companies as a structured path to explore the possible ways they can increase their manufacturing flexibility.
Keywords: 000; Evaluation; Industry 4.0 (I4.0); I4.0 technological concepts; Manufacturing flexibility; Methodological approach